Endovascular Occlusion of Dural Cavernous Fistulas through a Superior Ophthalmic Vein Approach. Issue 5 (October 2013) - Briganti, Francesco; Caranci, Ferdinando; Leone, Giuseppe; Napoli, Manuela; Cicala, Domenico; Briganti, Giuseppe; Tranfa, Fausto; Bonavolontà, Giulio
Dural cavernous fistulas are low-flow vascular malformations with usually benign clinical course and a high rate of spontaneous resolution. Cases with symptom progression must be treated with an endovascular approach by arterial or venous route. We report 30 patients with dural cavernous fistulas treated by coil embolization using surgical exposure and retrograde catheterization of the superior ophthalmic vein (SOV). The procedure resulted in closure of the fistula without other endovascular treatments in all 30 patients and clinical remission or improvement in 20 and eight patients, respectively. Embolization via a SOV approach is a safe and easy endovascular procedure, particularly indicated for dural cavernous fistulas with exclusive or prevalent internal carotid artery feeders and anterior venous drainage.